Multi-grade teaching and learning in rural South Africa - Gawie Schlebusch; Myameko Pele (Revista de Educação PUC-Campinas)
This article aims to delve into the distinctive teaching and learning strategies utilised in multigrade classrooms situated in rural areas of the Free State Province, South Africa. Through an exploration of the intricacies inherent in these environments, the article aims to pinpoint effective teaching strategies tailored to meet the unique requirements of learners within this context. This qualitative study engaged 14 Intermediate Phase educators and 6 principals from multi-grade schools in the Lejweleputswa and Fezile Dabi education districts. Purposive sampling was utilised to select participants. Data collection involved semi-structured interviews, while qualitative thematic analysis, employing an interpretive qualitative approach, was utilised for data analysis. Teaching strategies in multi-grade classrooms exhibit notable diversity, shaped by factors such as teacher personality, subject matter, and classroom dynamics. The strategies employed in these settings reflect the teacher’s skills, lesson objectives, and the physical arrangement and space available in the classroom. However, both teachers and principals lack sufficient orientation or training in the specific strategies essential for effective multi-grade teaching.